3D CFD modelling and optimization of single‐phase flow in rotating packed beds. (14th April 2015) - Yang, Yucheng; Xiang, Yang; Li, Yingang; Chu, Guangwen; Zou, Haikui; Arowo, Moses; Chen, Jianfeng
<x xml:space="preserve">Abstract</x> Rotating Packed Beds (RPBs) are novel reactors used for intensification of mass transfer and mixing since they provide adjustable centrifugal force to simulate high gravity. In this work, in order to analyze and optimize fluid flow in RPBs, a three‐dimensional single‐phase flow was simulated and validated with previous experimental data. The results show that pressure drop increases with an increasing gas flow rate and rotation speed, and reveal the distribution of total pressure and velocity magnitude. A RPB with radial gas inlet, one of the generic types of RPBs, which is widely applied in the chemical industry but has poor gas distribution on the surface of packing, was optimized using various baffles. The width, distance, shape, and opening porosity of the baffles were examined by adopting a criterion, and their effect on gas distribution was illustrated. Finally, a possible optimum structure of the RPB was formulated under optimal operational conditions.